Establishing an Islamic Learning Habituation Through the Prophets’ Parenting Styles in the New Normal Era - Kana Safrina Rouzi; Nikmah Afifah; Ciptro Hendrianto; Desmita Desmita (International Journal of Islamic Educational Psychology, 2020)
The COVID-19 pandemic, which has plagued since the beginning of this year, has shifted life habits, including study habits. They have changed from using hard file-based media (books, paper, pens, and pencils) to soft file media (network-based media) because students must learn from home. The purpose of this paper is to describe the concept of learning habits integrated with Islamic Learning Habituation through the implementation of the Al-Qur'an verses, containing the Prophet's parenting style by presenting a sense of muraqabah (the supervision of Allah SWT). This research method used text study. The research's nature was descriptive analysis research with idealistic patterns in reducing the Al-Qur'an verses and other literature to find solutions to research problems. The literature search results found that muraqabah's feelings in children would result in Islamic learning habits, namely learning practices that prioritized honesty, trust, and responsibility when studying online without parents' company.